2019
DOI: 10.1002/ijc.32424
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical impact of TP53 germline mutations in Chinese women with breast cancer

Abstract: The prevalence and clinical relevance of TP53 germline mutations in a large unselected breast cancer series are largely unknown. Here, we determined TP53 germline mutations in a large cohort of 10,053 unselected breast cancer patients through multigene panel‐based next‐generation and/or Sanger sequencing assays. We found that 0.5% of patients (50 cases) carried a pathogenic TP53 germline mutation in this large series of 10,053 unselected breast cancer patients, and the prevalence of TP53 germline mutation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 29 publications
1
10
0
2
Order By: Relevance
“…However, 2 recent large-scale case-control studies of Caucasian women reported that the TP53 gene was not significantly associated with breast cancer risk 13 , 14 . This difference might be explained by the observation that the prevalence of TP53 pathogenic variants in Asian breast cancer patients was much higher than that in Caucasian breast cancer patients 9 , 13 , 14 , 31 . In addition, a previous study based on patients with Li-Fraumeni syndrome reported a very high relative risk of breast cancer (OR: 105) for the TP53 gene 27 .…”
Section: Discussionmentioning
confidence: 94%
“…However, 2 recent large-scale case-control studies of Caucasian women reported that the TP53 gene was not significantly associated with breast cancer risk 13 , 14 . This difference might be explained by the observation that the prevalence of TP53 pathogenic variants in Asian breast cancer patients was much higher than that in Caucasian breast cancer patients 9 , 13 , 14 , 31 . In addition, a previous study based on patients with Li-Fraumeni syndrome reported a very high relative risk of breast cancer (OR: 105) for the TP53 gene 27 .…”
Section: Discussionmentioning
confidence: 94%
“…In a large cohort study of Chinese women with breast cancer, Sheng et al (2020) identified patients possessing TP53 germline variants were more likely to respond to carboplatin-based (with or without anthracycline) neoadjuvant therapy compared to anthracycline or taxane-based regimens. Though future clinical studies are needed, these cohort findings represent a reasonable justification for choosing carboplatin-based therapy regimens in TP53 -variant breast cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Es necesario considerar que, por un lado, aún en las pacientes con mutaciones en los genes de alto riesgo para el desarrollo de cáncer de mama, o con historia familiar de cáncer de mama, los segundos primarios mamarios suelen diagnosticarse en estadios más tempranos y con positividad para los receptores hormonales 50 . Y por otro lado, que el pronóstico global de las pacientes con SLF y cáncer de mama lo determina la mutación per se de TP53 y el caso índice, es decir, las características genéticas y clínico-patológicas de las pacientes y el primer tumor mamario 21 , 34 . Para la paciente presentada en este artículo, no solo el estado mutacional de TP53 21 , sino también el estadio clínico (IIIB), el subtipo biológico (luminal B, HER2 negativo) y la ausencia de respuesta patológica completa luego de la quimioterapia neoadyuvante, son variables que ya le están confiriendo un mal pronóstico, teniendo un riesgo de recurrencia y muerte por la enfermedad que se estiman en un 30,4% y 15,8% a 5 años, respectivamente 51 .…”
Section: Discussionunclassified
“…(20) sobre la supervivencia libre de enfermedad según las variantes patogénicas en TP53, se encontró que el tiempo para el diagnóstico entre el primero y el segundo cáncer fue significativamente menor en portadores de translocaciones y "hotspots", comparado con otro tipo de variantes. Por otro lado, Sheng, et al (21) señalaron que la mutación en TP53 es un factor independiente de mal pronóstico, pues, en general, las pacientes con SLF y cáncer de mama tienen una mortalidad del 18% a 5 años, comparada con el 5% en aquellas pacientes con cáncer de mama que no son portadoras de la mutación. Esta diferencia se mantiene incluso después de 10 años de seguimiento, con supervivencias del 77% y 90%, respectivamente.…”
Section: Introductionunclassified